2017
DOI: 10.1126/scisignal.aaj1784
|View full text |Cite
|
Sign up to set email alerts
|

The matricellular protein TSP1 promotes human and mouse endothelial cell senescence through CD47 and Nox1

Abstract: Senescent cells withdraw from the cell cycle and do not proliferate. The prevalence of senescent compared to normally functioning parenchymal cells increases with age, impairing tissue and organ homeostasis. A contentious principle governing this process has been the redox theory of aging. We linked matricellular protein thrombospondin 1 (TSP1) and its receptor CD47 to the activation of NADPH oxidase 1 (Nox1), but not of the other closely related Nox isoforms, and associated oxidative stress, and to senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 83 publications
(139 reference statements)
4
56
0
Order By: Relevance
“…Aging itself was sufficient to upregulate arterial TSP1 and CD47 expression, while simultaneously downregulating essential self-renewal factors genes (OSKM) in rodent and human arteries. These data are in line with reports of increased renal and myocardial TSP1 expression with age [41,42] and extend our previous findings in human pulmonary arteries that TSP1 expression positively correlated with advancing age [20]. Together, our data support the idea that vascular CD47 expression is age-sensitive.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Aging itself was sufficient to upregulate arterial TSP1 and CD47 expression, while simultaneously downregulating essential self-renewal factors genes (OSKM) in rodent and human arteries. These data are in line with reports of increased renal and myocardial TSP1 expression with age [41,42] and extend our previous findings in human pulmonary arteries that TSP1 expression positively correlated with advancing age [20]. Together, our data support the idea that vascular CD47 expression is age-sensitive.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, arterial rings from aged CD47-null mice had cell sprouting comparable to vessels from young mice ( Figure 4 G,H), which was persistently greater than sprouting from aged WT animals ( Figure 4 H,I). TSP1 has previously been implicated in aging and inflammation [ 20 , 27 ]. To determine whether the effects of CD47 are cell autonomous or dependent on TSP1 in aged arteries, we monitored angiogenic sprouting in aged WT and CD47-null aortic rings after incubation with exogenous TSP1 (2.2 nM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the lack of CD47 expression in endothelial cells enabled these cells to spontaneously gain characteristics of embryonic stem cells [30]. More recent reports revealed that TSP1 promotes ROS generation via the up-regulation of Nox1 [63]. The current data confirmed that the process of angiogenesis was inhibited as a function of diabetes both in in vitro and in vivo sponge model of wound healing.…”
Section: Discussionsupporting
confidence: 70%
“…CD47 has high binding affinity to SIRPa, TSP-1 and other integrin molecules on platelets, sickle red blood cells, microglia, B lymphocytes, etc. [ 51 , 52 , 53 , 54 , 55 ]. Due to the varieties of binding molecules, the type of signal induce by CD47 depends on the type of ligand and the condition on which the binding occur.…”
Section: Role Of Cd47 In Immune Responsementioning
confidence: 99%